Using Mindfulness to Reduce Anxiety and Depression of Patients With Fever Undergoing Screening in an Isolation Ward During the COVID-19 Outbreak - Liu, Yuping; Huyang, Sizhu; Tan, Haihong; He, Yubiao; Zhou, Jin; Li, Xue; Ye, Man; Huang, Jin; Wu, Daxing (Frontiers in Psychology, 2021)
The coronavirus disease 2019 (COVID-19) continues to spread globally. This infectious disease affects people not only physically, but also psychologically. Therefore, an effective psychological intervention program needs to be developed to improve the psychological condition of patients screened for fever during this period. This study aimed to investigate the effect of a brief mindfulness intervention on patients with suspected fever in a screening isolation ward awaiting results of the COVID-19 test. The Faces Scale and the Emotional Thermometer Tool were used to investigate 51 patients who were randomly divided into an intervention group and a control group. All patients completed self-rating questionnaires online at the time they entered the isolation ward and before they were informed of the results. The intervention group listened to the mindfulness audios through hospital broadcasts in the isolation ward before their lunch break and while they slept. Compared with the control group, the intervention group’s life satisfaction score increased (F = 4.02, p = 0.051) and the emotional thermometer score decreased (F = 8.89, p = 0.005). The anxiety scores (F = 9.63, p = 0.003) and the needing help scores decreased significantly (F = 4.95, p = 0.031). Distress (F = 1.41, p = 0.241), depression (F = 1.93, p = 0.171), and anger (F = 3.14, p = 0.083) also decreased, but did not reach significance. Brief mindfulness interventions can alleviate negative emotions and improve the life satisfaction of patients in the isolation ward who were screened for COVID-19 during the waiting period.